COMPAS runs for autonomous vehicles scenarios - Vuk, Goran (Proceedings from the Annual Transport Conference at Aalborg University, 2017)
OTM is a tour based traffic model for the Greater Copenhagen. A shift of modelling of person travel demand to an activity based approach has been tried since 2011 through a development of the COMPAS model. This paper is a first Danish evidence of differences between the results of the two models for the same (or similar) scenario runs. For the case study of scenario runs for autonomous vehicles (AV), we conclude that the tour based and activity based approaches to modelling of person travel demand result indeed in quite different results. Three largest evidences for this statement are the following: The effect of changing the carpark into AV is considerably stronger in OTM than in COMPAS, i.e. the increase in car trips is larger in OTM than in COMPAS. Slow modes contribute most to the new car trips in OTM runs. However, in COMPAS it is the PT trips that shift largely to AVs. The very short trips, i.e. walk, do not change to car trips in the COMPAS AV scenario runs. Actually, the walk trips increase alongside the car trips due to the positive induced traffic. Opposite to that, in all OTM runs the walk trips drop, sometimes quite much.